KESULITAN ANALITIK ASPEK MENYIMAK SISWA KELAS IV SEKOLAH DASAR - Rohadatul Husna; Khirjan Nahdi; Zulfadli Hamdi; Muhammad Husni (Universitas Muhammadiyah Purwokerto, 2023)
This study aims to determine the analytical difficulties of listening aspects of fourth grade students of SDN 02 Teros in the 2021/2022 academic year. The data source used is the primary data source, where the researcher gets the data directly without going through an intermediary. This research is a descriptive quantitative research. The population in this study were all fourth grade students with a total of 30 students. This research variable uses one variable or called a single variable, namely the analytical difficulty of listening aspects. The data collection technique used a test in the form of a command to find out the analytical difficulties of students' listening skills using fiction reading materials and interviews. The results of the data obtained by researchers after conducting research by obtaining an average score of 60.16 students with a total of 24 students with a percentage of 80% who could not meet the Minimum Completeness Criteria (KKM) which stated that most of the fourth grade students of SDN 02 Teros in the subject of 2021/2022 has difficulty in analyzing the listening aspect.